Pengenalan E-Commerce: Peluang dan Tantangan bagi UMKM Desa Sikeben Kecamatan Sibolangit Kabupaten Deli Serdang - Cahaya Aqila; Dewi Santri; Muhammad Abdillah; Luthfiah Mianda; M. Fakhriza (Pusat Riset dan Inovasi Nasional, 2026)
MSMEs in Sikeben Village have the potential to sell their products widely because the quality of their products is competitive with those of other MSMEs. Currently, MSMEs in Sikeben Village face limitations in accessing wider markets due to their conventional marketing systems. This condition has resulted in the potential of local products, which actually have high selling value, being less known to consumers outside the Sikeben village area. This is evidenced by the fact that, to date, no MSMEs in Sikeben Village have utilized e-commerce to sell their products. Through this activity, the people of Sikeben Village were introduced to the use of e-commerce as a medium for online promotion and sales, while also identifying obstacles that arise in the introduction of e-commerce websites. This community service program was carried out through direct training in Sikeben Village. This community service program was carried out through direct training in Kampai Village using the Participatory Action Research (PAR) method. As a result of this activity, MSMEs began to learn how to use Facebook to market their products. Participants were taught how to create business pages, upload products, and promote them in order to reach buyers outside Sikeben Village.